A highly selective fluorescent probe for sensitive detection of HAV in water. Issue 26 (18th June 2019) - Xie, Jun; Zhou, Peng; Wen, Min; Bai, Jingyu; Yang, Fangming; Duan, Chunying
Abstract : Highly specific and sensitive detection of hepatitis A virus (HAV) in water is of great significance for drinking water safety and epidemic control. Abstract : Highly specific and sensitive detection of hepatitis A virus (HAV) in water is of great significance for drinking water safety and epidemic control. In this work, a hybrid nanobiosensor for HAV detection was established based on fluorescence resonance energy transfer (FRET) between quantum dots (QDs) as a donor and Cy5 as an acceptor. Transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy and dynamic light scattering were used to characterize the chemical and physical structures of the hybrid biosensor. Under optimized conditions, the detection limit of target DNA (tDNA) was 1.3 × 10 −11 mol L −1 (S/N = 3), with a linear range of 2 × 10 −10 mol L −1 to 5 × 10 −8 mol L −1 . In addition, it showed excellent selectivity in the presence of various interfering species. The results show the applicability of the biosensor for monitoring HAV in environmental and food samples.